Validity of a food frequency questionnaire to assess food intake in Mexican adolescent and adult population - Edgar Denova-Gutiérrez; Ivonne Ramírez-Silva; Sonia Rodríguez-Ramírez; Alejandra Jiménez-Aguilar; Teresa Shamah-Levy; Juan A Rivera-Dommarco (Instituto Nacional de Salud Pública, 2016)
Objective. To assess the validity of a 140-item semi-quantitative food frequency questionnaire (SFFQ), in Mexican adolescents and adults. Materials and methods. Dietary intakes using a SFFQ and two 24-hour dietary recalls (24DRs),in nonconsecutive days during the same week were measured from 178 adolescents and 230 adults participating in the Mexican National Health and Nutrition Survey-2012. Validity was evaluated using correlation coefficients (CC), deattenuated CC, linear regression models, cross-classification analysis, and the Bland-Altman method. Results. In adults, deattenuated correlation coefficients between the SFFQ and the 24DRs ranged from 0.30 for folate to 0.61 for saturated fat. In addition, 63% adults and 62% adolescents were classified in the same and adjacent quartile of nutrient intake when comparing data from SFFQ and 24DRs. Conclusions. The SFFQ had moderate validity for energy, macronutrients and micronutrients. It also had good validity to rank individuals according to their dietary intake of different nutrients.